Numerical Analyses of Soft Soil Reinforced with GEC. (2016) - Gioffrè, Domenico; Castelli, Francesco; Fiumara, Claudio; Moraci, Nicola
Abstract: Construction of embankments on soft soil may be a challenge, owing to its low shear strength and high compressibility. Among the different methods of ground improvement, the geosynthetic encased columns (GEC) are often used to support embankments over soft soil. In order to evaluate the mechanical response of the geosynthetic encased columns, based on the soil and column properties, settlements and stresses can be determined by means of analytical solutions or numerical analyses. The paper compares the results of these two approach by means of parametric analyses. The German regulation EBGEO proposed an analytical model for predicting the pressure-settlement response of an axisymmetric unit cell of clay with a GEC. The numerical simulation of the behavior of a GEC in soft clay loaded by an embankment has been carried out by means of a two-dimensional finite-element commercial code.